2012
DOI: 10.1530/eje-12-0388
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid carcinoma: the influence of policy changing in clinical characteristics and disease progression

Abstract: Objective: Medullary thyroid carcinoma (MTC) has varying clinical course. We assessed trends in MTC presentation during the last 34 years. Design: Retrospective study. Methods: One hundred and fifty one patients (44.4% males) were followed for 0.9-34 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…In recent years, the incidence of small thyroid cancer has increased globally mainly as a result of thyroid ultrasound screening . Consistent with this, changes over time in clinicopathological characteristics, outcomes and prognostic factors for differentiated thyroid cancer (DTC) have been reported. In a similar manner, increases in thyroid screening with ultrasound and measurement of serum calcitonin in subjects with thyroid nodules might have led to earlier detection of smaller MTCs.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In recent years, the incidence of small thyroid cancer has increased globally mainly as a result of thyroid ultrasound screening . Consistent with this, changes over time in clinicopathological characteristics, outcomes and prognostic factors for differentiated thyroid cancer (DTC) have been reported. In a similar manner, increases in thyroid screening with ultrasound and measurement of serum calcitonin in subjects with thyroid nodules might have led to earlier detection of smaller MTCs.…”
Section: Introductionmentioning
confidence: 69%
“…Therefore, the clinicopathological characteristics and prognosis of MTC might also change over time. However, the reported prognosis or predictive factors for MTC were mainly based on patients diagnosed before early 2000, and changes in clinicopathological features or prognosis over time have been rarely reported …”
Section: Introductionmentioning
confidence: 99%
“…In this retrospective study of MTC patients, we aimed to investigate whether tumour size could be of prognostic value for the clinical behaviour of MTCs, especially of smallMTCs (%1.5 cm); the aggressiveness of larger tumours has previously been shown (1,13,16,19,20). We divided smallMTCs into four size subgroups roughly representing quartiles and compared the clinical features between subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…There was a strong association between the intratumoral lymphatic vessels and regional lymph node metastases for papillary thyroid carcinomas, suggesting that proliferation and invasion of new lymphatic vessels into the tumor play a role in its spread through lymphatic vessels [4]. Follicular thyroid carcinomas metastasize to the distant organs through hematogenous spread rather than through lymph spread [8].…”
Section: Discussionmentioning
confidence: 99%
“…Machens and Dralle analyzed 715 cases of MTC and found that 10%, 8% and 5% were diagnosed with lung, liver and bone metastasis, respectively [3]. Recently, there is an increased detection of micro-MTC thanks to the routine measurement of serum calcitonin levels [4]. Sporadic MTCs account for 80% of the carcinomas whereas 20% have a familial basis [5] [6].…”
Section: Introductionmentioning
confidence: 99%